(untitled) - Valpuesta, Victoriano (Boca Raton, 2002)
The book begins with an analysis of the available tools and methods, from the selection and isolation of genes to safety issues such as the stability of transgenes. The contributors discuss the range of properties that have been the subject of genetic enhancement, including agronomic traits such as fruit quality and resistance to environmental stresses, as well as sensory properties such as color, flavor, processing functionality, and nutritional quality. In addition, the text also examines the use of molecular markers in plant breeding. The subsequent chapters consider how biotechnology can improve plant defense mechanisms and also extend the post-harvest life of fruit and vegetables.
Keywords: Agricultural biotechnology,Genetically modified foods,Fruit,Vegetables; Genetics,Genetics